Studi Pemahaman Penumpang terhadap Barang Terlarang (Prohibited Items) di BLU UPBU Kelas I Utama Juwata Tarakan - Atmaja, Fikriansyah Cakra; Sundoro; Lestary, Dwi (Jurnal Ground Handling, 2025)
This study aims to evaluate the level of passenger understanding regarding prohibited items in air travel and to assess the effectiveness of information dissemination efforts at BLU UPBU Kelas I Utama Juwata Tarakan Airport. A qualitative descriptive method was applied through observations, structured interviews with aviation security personnel and passengers, surveys using questionnaires distributed to 50 respondents, and documentation analysis from logbooks at Passenger Security Check Points (PSCP). The findings reveal that only 22% of passengers correctly understand regulations regarding prohibited items, while 44% were unsure, and 34% lacked knowledge. In particular, misunderstandings were significant regarding the carriage of lighters and sharp objects, which are consistently the top three confiscated items during security checks. Furthermore, 76% of respondents stated that they find it difficult to access safety-related information at the airport. Current communication methods, such as videotrons, posters, and social media, have not been fully optimized for delivering essential safety messages. The study highlights the need for improved educational strategies using visual aids, digital platforms, and direct communication by airport personnel. These findings underline the importance of more inclusive, accessible, and proactive safety campaigns to increase compliance and ensure safer airport operations.